Development of plasma technology at the University of Malaya - Wong, C.S.; Moo, S.P.; Chew, A.C.; Lee, S. (1999)
In this paper, programs carried out at the University of Malaya by the Plasma Reseach Group to develop four types of plasma technology will be reviewed. These are (1) plasma fusion; (2) pulsed plasma radiation/particle sources for x-ray microlithography and microscopy, for neutron interrogation of matter and for ion implantation; (3) RF inductively coupled plasma system for material processing; and (4) plasma ozonizer for water and waste treatments.